KINETICS STUDY FOR HEAT TOLERANCE OF LDPE DEGRADING STRAINS - MERINA PAUL DAS; SANTOSH KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Some microorganisms are sensitive to heat. They do not survive if subjected to higher temperature for longer duration. In this research, two bacterial isolates were screened and identified as Bacillus amyloliquefaciens BSM-1 and Bacillus amyloliquefaciens BSM-2 which are able to degrade the low density polymers. The thermal inactivation study was done for both isolates at four different temperature and survival curves were obtained for a specific temperature. The thermal death constants values are indicating that BSM-2 was more heat resistant than the BSM-1. This may be due to the synthesis of heat shock protein by BSM-2. Thus isolate BSM-2 was showed more heat tolerance and survived in higher temperature for maximum time and able to degrade the high percentage of polymers.